CYBER RISK MANAGEMENT IN THE DIGITAL ERA: AN ANALYSIS OF MITIGATION STRATEGIES AND PREVENTIVE INNOVATIONS AGAINST CYBERCRIME IN INDONESIA - Chalifa Luthfiyya Nadhifa; Ova Novi Irama; Anggia Sari Lubis; Junita Putri Rajana Harahap (PT. Jurnal Center Indonesia Publisher, 2025)
Cyber risk management has become a critical issue as the number of cybersecurity incidents continues to rise each year. This study aims to analyze the trends in cyber incidents, the most prevalent types of cybercrimes, and the efforts in mitigation and cyber risk management in Indonesia. According to data from the National Cyber and Crypto Agency (BSSN) for the period 2019 to 2023, the number of incidents increased significantly from 290,000 cases in 2019 to 1,031,389 cases in 2023. The dominant types of cybercrime shifted each year, starting with phishing in 2019, malware in 2020, ransomware in 2021, DDoS attacks in 2022, and data breaches in 2023. This surge in incidents reflects the growing complexity of cyber threats faced by various sectors in Indonesia. In response, the government and private sector have strengthened regulations through the enactment of the Personal Data Protection Law and have adopted technologies such as artificial intelligence (AI) and blockchain to enhance detection and prevention of cyberattacks. Effective cyber risk management requires integrated preventive, detective, and corrective measures to safeguard information systems and sensitive data from increasingly sophisticated attacks. Through collaboration among the government, private sector, and the public, Indonesia’s digital ecosystem is expected to become more secure and resilient in the face of cybercrime threats..